PHARMACOGNOSTICAL AND PHYTOCHEMICAL ANALYSIS OF STEM PART OF THE TRADITIONAL HERB: ZALEYA GOVINDIA - Sharma Shailendra; Anil, Bhandari (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: The objective of the study is to cover the pharmacognostical and preliminary phytochemical screening of Zaleya govindia. The stem of Zaleya govindia belonging to the family Aizoaceae is a widely grown plant throughout India. Method: Pharmacognostical study included macroscopical characters, physico-chemical constants and fluorescence analysis. Result: The powder characteristics showed presence of calcium oxalate crystals, starch grains, fibers, trichome, mucilage and lignified cells. Different ash values were determined to find the inorganic content in the sample. Physiochemical studies revealed, foreign matter (0.52Â±0.01w/w), total moisture content (Stem-6.66%w/w), total ash (Stem-15%w/w), acid insoluble ash (Stem-3.75%w/w), water-soluble ash (Stem-7.5%w/w), alcoholic soluble extractive value (Stem-13.33%w/w), chloroform soluble extractive value (Stem-10%w/w), pet-ether soluble extractive value (Stem-1.733%w/w), and water soluble extractive value (Stem-18.66%w/w). Solvents of different polarity were used to find out the extractive value for root of Zaleya govindia. Conclusion: Solvents of different polarity were used to find out the extractive value for stem part. Carbohydrate, glycoside, alkaloid, flavonoids, tannin and resin compounds were found in preliminary phytochemical screening. Ultraviolet analysis exhibited considerable variation. Phytochemical investigation indicated the preparation of different extracts using different solvents and phytochemical tests for confirmation of the presence of carbohydrate, alkaloids, glycosides, triterpenes, phytosterols, phenolic compounds, tannin, saponins, and flavonoids. T.S of stem with different reagents shows the presence epidermis, cortex, pith, vascular bundles, calcium oxalate crystals, starch grains etc. Key words: Pharmacognostical, Extractive value, phytochemical analysis, Fluorescence analysis.